Expression and purification of recombinant serine protease domain of human coagulation factor XII in Pichia pastoris. Issue 10 (3rd October 2019) - Peng, Bangya; Xue, Guangpu; Xu, Dongfang; Feng, Zanjie; Chen, Jing; Huang, Mingdong; Lu, Hongling; Gong, Lihu
ABSTRACT: Human coagulation factor XII, the initiating factor in the intrinsic coagulation pathway, is critical for pathological thrombosis but not for hemostasis. Pharmacologic inhibition of factor XII is an attractive alternative in providing protection from pathologic thrombus formation while minimizing hemorrhagic risk. Large quantity of recombinant active factor XII is required for screening inhibitors and further research. In the present study, we designed and expressed the recombinant serine protease domain of factor XII in Pichia pastoris strain X-33, which is a eukaryotic expression model organism with low cost. The purification protocol was simplified and the protein yield was high ( 20 mg/L medium). The purified serine protease domain of factor XII behaved homogeneously as a monomer, exhibited comparable activity with the human βFXIIa, and accelerated clot formation in human plasma. This study provides the groundwork for factor XII inhibitors screening and further research. Graphical abstract: : In this study, recombinant human coagulation factor XII was produced in P.pastoris with high yield. This recombinant protein exhibited full activity.